Ti3C2 MXene co-catalyst on metal sulfide photo-absorbers for enhanced visible-light photocatalytic hydrogen production - Jingrun Ran (Nature Portfolio, 2017)
Solar hydrogen production through photocatalytic water splitting requires active and stable co-catalysts to replace platinum. Here, the authors use DFT to identify Ti3C2nanoparticles as potential co-catalysts, and assess their photocatalytic hydrogen production activity.